Russian feminitives: what can corpus data tell us? - Nesset, Tore; Piperski, Aleksandr; Sokolova, Svetlana (Russian Linguistics, 2022)
Recent years have seen considerable debate concerning Russian feminitives, i.e. derived formations that designate female professionals, such as advokatka, advokatša, advokatessa, ženščina-advokat or advokat-ženščina that all refer to female lawyers. In this article, we investigate the use of feminitives based on data from the Araneum Russicum Maximum corpus and the Russian National Corpus. It is shown that the choice of feminitive to some extent depends on the morphophonological properties of the base word. It is furthermore argued that suffixed feminitives are more frequent than compounds like ženščina-advokat and advokat-ženščina, and that the distribution has changed over time. Suffixed feminitives reveal a stronger tendency to combine with gender-related epithets (e.g., obajatel’naja agentka ‘charming agent’), while the type ženščina-X is frequently used with the epithet pervyj ‘first’. Our article is an empirical study of the actual use of feminitives in corpus data, which we hope will inform future metalinguistic discussion and prescriptivist thinking about feminitives in Russian.<br
Keywords: Suffix; Word-formation; Corpus data; Compound; Russian; Feminitive